Peer Assessment untuk Mengembangkan Keterampilan Presentasi Pada Kegiatan Pelatihan Komunikasi Skill - Enny Diah Astuti; Sri Hastuti; Nika Sintesa; Yunita Indriany; Herry Syafrial (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
Education has an important role in developing skills, developing soft skills needed by students in facing the future and the world of work. Communication skills are a requirement that must be met in a highly competitive digital era. Peer assessment is an innovation in the assessment system. The benefits of peer assessment are providing feedback, cognitive and metacognitive processes, increasing motivation, collaborative learning processes, self- regulated learning, and improving performance. The method used in this study is a descriptive method by applying peer assessment to assess presentation skills. The results of the assessment carried out through peer assessment conducted by the participants with the assessment carried out by the trainer which was carried out briefly and simultaneously were considered effective enough to be applied in training activities. This can be seen from the emergence of similar assessments that reached 50% in the implementation of peer assessments as an effort to improve presentation skills and skills in communication skills training.